Operation and performance of three-phase asymmetric multi-leg power transformers subjected to nonlinear and dynamic electromagnetic disturbances - Moses, Paul S. (Curtin University, 2012)
Three-phase power transformers continue to be an important fixture in modern power systems since their initial development in the 1880s. While transformer design has fundamentally remained the same, the operating environment has significantly changed. This is apparent through new flexible network operations (e.g., integration of renewable energy sources), growing network complexities (e.g., deployment of micro-grids, smart grids, etc.) and increasing use of nonlinear power electronic equipment (e.g., power converters and motor drives). Thus the issue of power quality in power systems has become an important consideration to utilities and industries as the performance of electrical machines and devices could be adversely affected. This doctoral thesis focuses on the performance of three-phase power transformers under various nonlinear and dynamic electromagnetic disturbances in distorted power networks.The first part of this work is devoted to the development and improvement of nonlinear electromagnetic models of three-phase multi-leg transformer cores for the study of steady-state and transient electromagnetic disturbances. This is mainly achieved by developing new detailed magnetic models for ferromagnetic nonlinearities (e.g., hysteresis) as well as considering core asymmetry and magnetic couplings of core-leg fluxes in three-phase multi-leg iron-core structures. These combined effects have not been considered in conventional electromagnetic transient studies of transformers and are shown in this work for the first time to have a significant impact on predicted steady-state and transient electromagnetic behaviour.In subsequent parts of this thesis, the developed models are applied to the examination of selected nonlinear electromagnetic phenomena such as transformer operation in harmonically distorted power systems (e.g., terminal voltage distortions and nonlinear loads), dc bias caused by geomagnetically induced currents, ferroresonance, and no-load magnetisation and inrush current effects. Furthermore, based on the new modelling approaches, improved methods are presented for estimating transformer aging with wider applicability to three-phase transformers considering load and source imbalances with harmonic distortions.With the advent of newly emerging smart grids, the last part of this thesis is devoted to exploring future transformer operation in new smart grid operating conditions such as plug-in electric vehicle charging. Transformer loading patterns with random uncoordinated PEV charging compared to coordinated charging activity in smart grids is investigated. The investigation highlights the notion of harnessing future smart grid technologies to better manage transformer health and performance.